Implementasi Program Adiwiyata dalam Mewujudkan Nilai-Nilai Pendidikan Islam di MTs Negeri 3 Pamekasan - Megawati Fajrin (Prodi PAI Fakultas Tarbiyah IAI Miftahul Ulum, 2022)
Madrasah is generally seen as an educational institution that is not only oriented towards cognitive development of students, but rather emphasizes the internalization of educational values ​​that can lead to moral nobility and maturity of thinking. Madrasa authority in this case is to guide, foster, and instill the cultivation of environmental care characters. Some natural events in this decade did not occur without cause but were triggered by human activities that exploited natural resources and the environment without limits. To overcome this, one of the steps that can be takento change the way of viewing and human behavior towards nature fundamentally through environmental ethics that can never be separated from the value of Islamic educational perspective. Environmental education, is providing insight into skills in environmental management which have been taught from an early age how to care about the environment, care for the earth, manage waste, use natural resources sparingly. Madrasa as an institution that has the authority to educate, guide, foster and accustom in learning including environmental issues. Islam comes with the value of rahmatanlil-alamin with a concern for the Islamic perspective environment, so adiwiyata is the right solution for life. This type of research is a case study with a qualitative approach. This study examines the value of Islamic education in the adiwiyata program, then the implementation of the adiwiwyata program in realizing the value of Islamic education, and the impact of the adiwiyata program on student behavior in realizing the value of Islamic education.